El realismo mágico en del amor y otros demonios de Gabriel García Márquez - Paccha Cuenca, Carolina Elizabeth (2014)
This paper, refers to one of the works of the writer Gabriel Garcia Marquez titled of love and other demons, where they review the presence of magical realism, focused to find the characteristic elements of this power which coexist the real and the magical, where is persive reality of what was life in Cartagena de Indias in the colonial, specifically in regards to slavery and to the presence of the Holy Inquisition as part of the demon of these peoples, and as these mystical beliefs, both representatives of the catholic religion and the American and African peoples are mixed and stand, result so an amalgam of cultures that can make us understand our reality. The methodology and applied techniques were used to construct a theoretical framework and be able to extract imformation based on true facts of the historical social aspects found in the work; they allowed infer on these realities and understand the message of the author, and at the sometime facilitate the conclusions and recommendations. The conclusions are determinated that in the novel are reprensentations of myths and legends American and African as opposed to the beliefs of the catholic churches, planes of reality and fantasy. From everyday reality which cobine with the imaginary, also evokes the history of our society and reminds us of those shrines to which they were subjected as many slaves as indigenous. This work is recommended to spread our culture and to do so, a notion of literature that our Latin American writers, have given us because they give us the possibility to reconnect with identifying elements of our culture should be.